2023
DOI: 10.1002/ijgo.15117
|View full text |Cite
|
Sign up to set email alerts
|

FIGO good practice recommendations on surgical techniques to improve safety and reduce complications during cesarean delivery

Inês Nunes,
Wanda Nicholson,
Gerhard Theron

Abstract: FIGO is actively contributing to the global effort to reduce maternal morbidity, mortality, and disability worldwide. Cesarean delivery rates are increasing globally, without signs of slowing down. Bleeding associated with cesarean delivery has become an important cause of hemorrhage‐related maternal deaths in many low‐ and middle‐income countries. Correct surgical techniques to improve safety and reduce complications of cesarean delivery is of the utmost importance. This article presents FIGO's good practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…Pregnancy-related risk factors for wound complications after CS include emergency CS, rupture of membranes and chorioamnionitis [20,29]. Surgical risk factors are operating time, surgeon experience, type of suture material, type of incision and abdominal wall closure and the use of antibiotics [14,21]. On the other hand, several evidence-based interventions have been shown to reduce the risk of post-cesarean wound complications, e.g., the administration of antibiotics within 60 min prior to skin incision, using chlorhexidine-alcohol for skin antisepsis and suture closure of the subcutaneous layer in women for whom its thickness is greater than 2 cm [21,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pregnancy-related risk factors for wound complications after CS include emergency CS, rupture of membranes and chorioamnionitis [20,29]. Surgical risk factors are operating time, surgeon experience, type of suture material, type of incision and abdominal wall closure and the use of antibiotics [14,21]. On the other hand, several evidence-based interventions have been shown to reduce the risk of post-cesarean wound complications, e.g., the administration of antibiotics within 60 min prior to skin incision, using chlorhexidine-alcohol for skin antisepsis and suture closure of the subcutaneous layer in women for whom its thickness is greater than 2 cm [21,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical risk factors are operating time, surgeon experience, type of suture material, type of incision and abdominal wall closure and the use of antibiotics [14,21]. On the other hand, several evidence-based interventions have been shown to reduce the risk of post-cesarean wound complications, e.g., the administration of antibiotics within 60 min prior to skin incision, using chlorhexidine-alcohol for skin antisepsis and suture closure of the subcutaneous layer in women for whom its thickness is greater than 2 cm [21,[33][34][35]. Temming et al demonstrated that the risk of wound complications was significantly lower in patients who received all the evidence-based interventions during CS in comparison to those who did not (20.3% vs. 28.1%, aRR 0.75, 95% CI 0.58-0.95), but the risk was still high and the authors concluded that there is a need for finding additional interventions that could be able to further reduce this risk [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations